The relationship variable tables and the percentages calculation in the research results presentation - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
The presentation of the results obtained in the research through statistical tables constitutes a moment of great importance within the research process corresponding to the specialty conclusion work. This article addresses two negative situations found with high frequency in this specific area of the final research report: the excessive and unjustified use of two-dimensional or variable relationship tables, and the inadequate presentation of the distribution of relative frequencies in these tables. Useful elements are offered for making decisions related to the crossing of variables in descriptive studies and with the calculation of percentages by rows, by columns or by the total number of cases, in these tables.